A methodological pilot study on oral health of young, healthy males - Vuokko Anttonen; Tarja Tanner; Antti Kämppi; Jari Päkkilä; Leo Tjäderhane; Pertti Patinen (Wolters Kluwer Medknow Publications, 2012)
Introduction: This study aimed to investigate the indications for an epidemiological survey on the oral health of young males, and the possibility of conducting it during their military service. Settings and Design: Despite the excellent oral health of young Finnish people in the past, there is concern about its degradation today. About 80% of young Finnish males enter the mandatory military service annually. The draftees have obligatory health inspection, with oral health screening, in the first two weeks of their service. Subjects and Methods: Self-reports on oral health were analyzed. Dental screening of conscripts performed by military dentists was timed and evaluated in two garrisons in 2010 (n = 256). Results: Over 40% of the conscripts reported having either dental symptoms or sensitivity after eating or drinking sour food or due to changes in temperature. Toothache was reported as having been the reason for the latest dental visit by 17% of the respondents. Clinical inspection took on an average almost three minutes and answering the questionnaire, almost 11 minutes. For evaluation of the process, the need for randomization of the study sample was emphasized as well as for specific guidelines, radiological education, and calibration of the dentists performing future survey to increase inter/intra examiner reliability. Moreover, the need for three computers per dentist for the questionnaires was pointed out. Discussion: The need for an epidemiological survey was indicated by a high number of respondents reporting dental symptoms and the need for treatment. An epidemiological survey is possible to be conducted by the existing military dental personnel, but they must be educated radiologically and calibrated. A specific protocol is essential.